IDENTIFICATION OF NOVEL TARGETS ENVIRONMENTAL STRESS TOLERANCE GENES IN PLANTS BY USING BIOINFORMATICS (Plant Bulletin, 2023)
The plant show retorts to the abiotic stresses which influence the biosynthesis of secondary metabolites in the plants. The current research identified novel genes in reference plants Prunus avium, Prunus persica, Mangifera indica, and Carica papaya, while as a model plant Arabidopsis thaliana was used. For this purpose, bioinformatics tools such as ORF, BLAST, and CDD tools were used. The Est of Prunus avium, Prunus persica, Mangifera indica, and Carica papaya were 30582, 26413, 38501, 20333 respectively. The genes HOS10, LOS4, MPK3, ELIP1, and DREB1A were analyzed through ORF, compared by BLAST, and CDD was used for searching of conserved domain database with nucleotide query coverage. The query coverage of all the genes in all four plants varies from 28% to 96% and the frame preferred are mostly +3 and +2, +1 is also present but in the very least form. The current research will help to comprehend the query coverage and define the identity of the selected genes in the cold and warm region's plants.
Keywords: Mentha longifolia; antioxidant activities; phenolic substance; flavonoid